Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
Answer:
0.002
Step-by-step explanation:
cuz
Answer:
The term that best describes a figure formed by three segments connecting three non-collinear points is:
Triangle.
Step-by-step explanation:
Step-by-step explanation:
We know that with the help of just one point we can't form any figure.
With the help of two points a line segment can be formed.
And with the help of three points if the three points are collinear a triangle can be formed.
Hence, the term that best describes a figure formed by three segments connecting three non-collinear points is:
Triangle.
Answer:
Wendy must mix .25 with .75
Step-by-step explanation:
Because 1 is a third of 3 which makes the process for the decimals.